Intersections in Christianity and Critical Theory - Falke, Cassandra. author. aut Link
XII, 196 p.
Keywords: Dealing with the historical and thematic intersections of Christianity and critical theory, this collection brings together a diversity of specialist scholars in the area. Building on recent discourses in theology as well as their knowledge of hermeneutic and critical traditions, they examine major themes in contemporary critical theory.